KERJASAMA PEMERINTAH KOTA BANDUNG DAN PT.TELKOM DALAM MEMBANGUN PROGRAM BANDUNG SMART CITY 2013-2014 - Yuditia . Bahrutsawab; Muhammad Adnan .; priyatno harsasto . (Journal of Politic and Government Studies, 2017)
This Reasearch discusses about how the realization of partnership that held by the City Government of Bandung and PT Telkom to build the Smart City program and any program as result from the partnership. This partnership is carried out by the Government of Bandung as a government effort to implement the principles of good governance at the local level by involving the business sector in regional development. The results showed that PT.Telkom is the one who takes a lead in the creation of programs of Smart City because of the resources they have are the most widely used than resources owned by the Government of Bandung. In regards to a form of partnership that was used is Build Operation and Transfer in the sense that PT.Telkom responsible for building facilities and infrastructures needed after creating such facilities operated and given ownership to the government as a grant, PT.Telkom was using CSR money to funded it. At the level of program implementation involves many government agencies in accordance with the program generated and therefore needs a decent supervision of the main actors of the partnership. in fact the Government of Bandung surveillance mechanism is so weak that the risk of poor performance of the program is still very possible. However this partnership has resulted programs of innovative public services as a support service improvements. It is expected that the government could improve the oversight function so that the continuity of the program can be guaranteed.Keywords: Partnership, Smart city, Public service